TPC status for MPD experiment of NICA project. (30th June 2017) - Averyanov, A.; Bazhazhin, A.; Chepurnov, V.F.; Chepurnov, V.V.; Cheremukhina, G.; Chernenko, S.; Fateev, O.; Kiriushin, Yu.; Kolesnikov, A.; Korotkova, A.; Levchanovsky, F.; Lukstins, J.; et al.
Abstract: In a frame of the JINR scientific program on study of hot and dense baryonic matter a new accelerator complex I on C ollider fA cility (NICA) based on the N uclotron-M is under realization. It will operate at luminosity up to 10 27 cm −2 s −1 for Au 79+ ions. Two interaction points are foreseen at NICA for two detectors which will operate simultaneously. One of these detectors, the Multi-Purpose Detector (MPD), is optimized for investigations of heavy-ion collisions. The Time-Projection Chamber (TPC) is the main tracking detector of the MPD central barrel. It is a well-known detector for 3-dimensional tracking and particle identification for high multiplicity events. The conceptual layout of MPD and detailed description of the design and main working parameters of TPC, the readout system based on MWPC and readout electronics as well as the TPC subsystems and tooling for assembling and integration TPC into MPD are presented.